Interface disorder as the cause for the kinetic Rashba-Edelstein effect and interface spin-Hall effect at a metal-insulator boundary - A. V. Shumilin; V. V. Kabanov (Physical Review Research, 2023)
The spin phenomena observed at a clean metal-insulator interface are typically reduced to the Rashba-Edelstein effect, which leads to spin accumulation over a few monolayers. We demonstrate that the presence of interface disorder significantly expands the range of potential phenomena. Specifically, the skew scattering at the metal-insulator boundary gives rise to the “kinetic Rashba-Edelstein effect,” where spin accumulation occurs on a much larger length scale comparable to the mean free path. Moreover, at higher orders of spin-orbit interaction, skew scattering is accompanied with spin relaxation resulting in the interface spin-Hall effect—a conversion of electrical current to spin current at the metal surface. Unlike the conventional spin-Hall effect, this phenomenon persists even within the Born approximation. These two predicted phenomena can dominate the spin density and spin current in devices of intermediate thickness.